Preoperative Protein Profiling Among Postoperative Cognitive Dysfunction (POCD) Patients Following Open-Heart Surgery: A Systematic Review and Integrated Bioinformatic Analysis - Marjanu Hikmah Elias; Nazefah Abdul Hamid; Sofwatul Mokhtarah Maluin; Shamsir Aris; Suhaini Kadiman; Kamilah Muhammad Hafidz; Norsham Juliana (MDPI, 2024)
Indexed by WOS/Scopus/ERA